2017
DOI: 10.1111/pcmr.12599
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory protein B7‐H3 promotes growth and decreases sensitivity to therapy in metastatic melanoma cells

Abstract: Subscribe to PCMR and stay up-to-date with the only journal committed to publishing basic research in melanoma and pigment cell biology As a member of the IFPCS or the SMR you automatically get online access to PCMR. Sign up as a member today at www.ifpcs.org or at www.societymelanomaresarch.org

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
54
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 50 publications
(72 reference statements)
4
54
0
Order By: Relevance
“…B7-H3 also promotes resistance to cancer drugs. A growing number of studies show that inhibition or reduced expression of B7-H3 increases the response of tumor cells to drugs that target DNA replication, alkylating agents, and inhibitors of PI3K/Akt/mTOR and Ras/Raf/MEK signaling [4,6,9,10]. This further supports B7-H3 as a target in anticancer therapy, alone or in combination with other existing therapeutic modalities.…”
Section: B7-h3 Induces Pro-oncogenic Traits Such As Cell Growth and Mmentioning
confidence: 85%
See 1 more Smart Citation
“…B7-H3 also promotes resistance to cancer drugs. A growing number of studies show that inhibition or reduced expression of B7-H3 increases the response of tumor cells to drugs that target DNA replication, alkylating agents, and inhibitors of PI3K/Akt/mTOR and Ras/Raf/MEK signaling [4,6,9,10]. This further supports B7-H3 as a target in anticancer therapy, alone or in combination with other existing therapeutic modalities.…”
Section: B7-h3 Induces Pro-oncogenic Traits Such As Cell Growth and Mmentioning
confidence: 85%
“…High-levels of soluble isoform are detected in the serum of cancer patients [3], which suggests soluble B7-H3 as a potential non-invasive biomarker. Finally, B7-H3 protein has also been found in the secretome, including exosomes and other extracellular vesicles [4]. B7-H3 is also expressed in tumor-associated endothelial cells, and high expression levels are associated with advanced tumor grade.…”
mentioning
confidence: 99%
“…B7-H3 is multifunctional but also noted for its dual role in immunoregulation and tumorigenesis compared to other immune checkpoints [13][14][15]. On the one hand, the role of B7-H3 in the tumor immunoregulation remains inconclusive; on the other, the function of B7-H3 and its downstream molecule in the proliferation and progression of tumor is incomplete.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging studies have also demonstrated that B7-H3 may contribute to the resistance of anti-cancer drugs with various mechanisms. Proliferation and glycolytic capacity of metastatic melanoma cells were found to decrease when expression of B7-H3 was reduced or inhibited, leading to reduced resistance to chemotherapy as well as other targeted therapies [39]; this mechanism was further demonstrated to involve the inactivation of p38 MAPK signaling [40]. Similarly, glycolytic capacity was increased with the overexpression of B7-H3 in tumor cells, which induced the resistance to API-2 (triciribidine) and everolimus (RAD-001) [41].…”
Section: Roles Of B7-h3 In Tumor Progression and Drug Resistancementioning
confidence: 99%